Autorytet pierwszoosobowy i samowiedza w koncepcji Crispina Wrighta - Miczke, Ida (Filozofia Nauki, 2020)
The aim of this paper is to analyze Crispin Wright’s constitutivist account of self-knowledge and first-person authority. Wright offered an alternative to standard detectivist theories of selfknowledge and first-person authority. According to his proposal, the subject does not detect her mental states, but rather creates them. Wright offered his proposal as a result of considering the problem of rule-following. In the paper, I describe Wright’s solution and analyze its problems. I claim that these problems render his theory unconvincing, and I try to uncover the sources of his failure. First of all, I claim that Wright did not get rid of picturing self-knowledge as a kind of perception, and I suggest that some problems within his theory are the same as those within perceptual theories of self-knowledge. I then turn to problems with the interpretation according to which Wright presents first-person authority as a product of our mental discourse only. Finally, I present an outline of a solution to the problems of Wright’s theory in which I follow David Finkelstein’s neo-expressivist proposal. I argue that an expressivist solution can be obtained by considering Fred Dretske’s conciliatory skepticism and that investigating Dretske’s account enables one to understand why Wright’s question concerning the relationship between the subject and her mental states is ill-formulated.